Hadith #383 - Sahih al-Bukhari - Ibrahim al-Nakha'i إبراهيم النخعي (Sahih al-Bukhari)
Hammam bin Al-Harith said, “I saw Jarir bin `Abdullah urinating. Then he performed ablution and passed his (wet) hands over his Khuffs (socks made from thick fabric or leather), stood up and prayed. He was asked about it. He replied that he had seen the Prophet (ﷺ) doing the same.” They approved of this narration as Jarir was one of those who embraced Islam very late.
Grade: Sahih

Hadith #1236 - Sahih al-Bukhari - Ibrahim al-Nakha'i إبراهيم النخعي (Sahih al-Bukhari)
Once a meal was brought to `Abdur-Rahman bin `Auf and he was fasting. He said, “Mustab bin `Umar was martyred and he was better than I and was shrouded in his Burd and when his head was covered with it, his legs became bare, and when his legs were covered his head got uncovered. Hamza was martyred and was better than I. Now the worldly wealth have been bestowed upon us (or said a similar thing). No doubt, I fear that the rewards of my deeds might have been given earlier in this world.” Then
Grade: Sahih